Intergenerational transmission of personality disorder: general or disorder-specific? - Auty, Katherine M. (Psychology, crime & law, 2022)
This study investigates intergenerational relationships between the father’s personality disorder (PD) traits and the PD traits of his male and female offspring. We examine whether the intergenerational transmission of PD is due to the father transmitting a general vulnerability to all PDs, or whether the transmission is more specific to particular PDs. Structural Equation Modelling techniques are used to investigate a hypothesised model, based on Livesley’s [(2007). A framework for integrating dimensional and categorical classifications of personality disorder. Journal of Personality Disorders, 21(2), 199–224. https://doi.org/10.1521/pedi.2007.21.2.199] conceptualisation, which reorganises the DSM PD traits into four dimensions: Emotional Dysregulation, Dissocial Behaviour, Inhibitedness, and Compulsivity. General and specific transmission effects are examined for each model. The data comes from the Cambridge Study in Delinquent Development, a large-scale prospective longitudinal survey of 411 males and their biological offspring. Findings revealed that the intergenerational transmission of PD traits from fathers to female offspring appeared to be both general and disorder-specific. Firm conclusions could not be drawn about the intergenerational transmission of PD traits from fathers to male offspring, as the data did not fit the hypothesised model.